Management of the Competitiveness of the Region in the Context of Sustainable Development Based on the Concept of "Evidence-Based Policy" - TUREKULOVA, Dametken; DULAMBAYEVA, Raushan; MUKHAMBETOVA, Lyazzat; NIYAZOV, Mussa; ABZHAPPAROVA, Aibope; OMAROVA, Ainura (Journal of Environmental Management and Tourism, 2022)
Competitiveness is an important factor of economic development, reflecting the ability to achieve and maintain high rates, thereby determining the economic growth of the country, competing in the international arena, and managing all necessary resources. Many scientists consider this concept, but, nevertheless, there is still no specific method for assessing the competitiveness of the country's regions. Therefore, the author considers methods of assessing competitiveness at the regional level in Kazakhstan using statistical data on the Karaganda region from the data of JSC "Kazpost". The purpose of the study is to analyze the management of the region's competitiveness in the context of sustainable development of Kazakhstan based on the concept of "Evidence-based policy" and develop recommendations for further improvement of measures aimed at protecting the environment on the materials of JSC Kazpost.